A model of the characteristics of hand grip muscle force based on elite female handball players of various ages - Dopsaj, M.; Valdevit, Z.; Vuckovic, G.; Ivanovic, J.; Bon, M. (Kinesiologia Slovenica, 2019)
The aim of the study was to establish trends in the development of contractile characteristics of hand grip in terms of the maximum and relative force, as a test for upper body strength. The sample consisted of 207 female handball players organised into age categories; 52 senior (age = 24.5 ± 3.3), 51 junior (U18, age = 17.4 ± 0.7), 45 youth (U16, age = 15.5 ± 0.9), and 49 young players (U14, age = 13.4 ± 0.5). There is a statistically significant difference of absolute and relative maximal hand grip muscle force between all age groups (Wilks`s lambda = 0.416, p = 0.000). The results showed that the values of the maximum right hand grip force ranged from 430.7 N to 297.7 N and from 405.5 N to 268.6 N for left hand for senior to young players, respectively (Table 1). Also, according to the results it was determined that trend of change in observed contractile characteristics according to the age groups are 44.7N and 43.6N for absolute, and 0.462 and 0.463 N·BW-1 for relative values of maximal hand grip force for the right and the left hand, respectively.